2019
DOI: 10.3390/educsci10010010
|View full text |Cite
|
Sign up to set email alerts
|

Representations and Concepts of Borders in Digital Strategy Games and Their Potential for Political Education in Geography Teaching

Abstract: In Germany, 93% of young people between the ages of 10 and 18 play video games daily. Political geography, in particular popular geopolitics, have found that video games can help to establish and develop people’s understanding of geopolitics. Consequently, this affects geography education, providing both challenges and opportunities for teaching. Geography teaching is an integral part of political education as students need to understand how boundaries and territories create spaces with regards to social power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…This situation raises the following questions for researchers and geography educators: Educational subject-based game design and implementation; how to use the necessary technology; how to provide widespread and cheap access to these games; how to approach games in pedagogical terms, which games to choose, and teacher training; how games can be updated with feedback, and how necessary cooperation and promotion can be provided; and it raises the questions of how to collect concrete data on learning outcomes of games, and it brings up new research areas. Seidel et al (2020) mentioned that all students may not be able to purchase or access digital games and suggested that these games should be implemented in the classroom under the supervision of a student who is an expert in the game. They stated that if there are no experienced students in the classroom, it is possible to use Let's Play videos on platforms such as YouTube where these games are presented on the Internet.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This situation raises the following questions for researchers and geography educators: Educational subject-based game design and implementation; how to use the necessary technology; how to provide widespread and cheap access to these games; how to approach games in pedagogical terms, which games to choose, and teacher training; how games can be updated with feedback, and how necessary cooperation and promotion can be provided; and it raises the questions of how to collect concrete data on learning outcomes of games, and it brings up new research areas. Seidel et al (2020) mentioned that all students may not be able to purchase or access digital games and suggested that these games should be implemented in the classroom under the supervision of a student who is an expert in the game. They stated that if there are no experienced students in the classroom, it is possible to use Let's Play videos on platforms such as YouTube where these games are presented on the Internet.…”
Section: Resultsmentioning
confidence: 99%
“…They stated that if there are no experienced students in the classroom, it is possible to use Let's Play videos on platforms such as YouTube where these games are presented on the Internet. Seidel et al, (2020) stated that teachers should be aware of the possibilities and challenges of new media, and teachers' media pedagogical support or their pedagogical specialization in media are also important elements in using the learning potential of computer games.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations